What Do They Do? Construction of a Team Leader Intervention Model - Ledin, Kjell; Bengtsson, Peter; Ärlemalm, Tore (Frontiers in Psychology, 2021)
This work was aimed to construct a model of team leader interventions in meetings when unexpected events arise. In thfe continued research this model will be used as a starting point for constructing and validating an inventory for team leader interventions. Empirical material was obtained from senior candidates, as they were able to propose as many interventions as possible in 10 different group meeting situations. The proposals provided an empirical basis with 327 proposals for a conceptual frame which was revised into six categories; Control, Inform, Initiate, Investigate, Support, Avoid. The Control category corresponds to Authoritative Leadership and Task Behaviour (Structure). The Support category corresponds to Democratic Leadership and Relationship Behavior (Consideration) The Avoid category is not taking leadership and letting events pass which corresponds to the Laissez-Faire Leadership. Three new categories could be added to the classical leadership theory. The Inform category that appears to be related to the controlling function. When the leader clarifies goals and paths to the goal it is indirectly a controlling function. The Initiate category is related to launching procedural or distracting activities. The Investigate category is actually obvious. Before controlling, informing, initiating, supporting or avoiding the leader ought to investigate the causes to the disorder and then decide which intervention is most appropriate.